Fetal ductus venosus Doppler as a predictor of pregnancy outcome - Hewidy, Medhat S.; Hagras, Ahmed M.; Elnamoury, Mohamed M.; Hendy, Heba M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The ductus venosus (DV) transports oxygenated blood to the developing heart and brain by avoiding the hepatic circulation. Due to the anatomical location of the DV, measurement of DV blood flow velocity waveforms indirectly disclose the cardiac functions and health of the foetus, which represents the pressure gradient between the umbilical vein and right atrium. The aim of this study was to evaluate the value of ductus venosus pulstality index of veins in early pregnancy in prediction of adverse pregnancy outcomes. Methods: 50 pregnant women with a single viable foetus between 13 and 24 weeks participated in this prospective cross-sectional study from 2021 to 2022 at Tanta University Hospital. Results: PI in normal group ranged from 0.80-1.20 with mean value 0.90±0.130 and in abnormal group ranged from 0.46-0.50 with mean value 0.522±0.069. S/a ration in normal group ranged from 1.74-3.18 with mean value 2.30±0.40 and in abnormal group ranged from 1.50-2.05 with mean value 1.833±0.212. There was statistically significant difference between outcomes of pregnancy with ultrasound findings (p<0.05). Conclusions: Numerous foetal disorders that might result in cardiovascular deterioration and other aberrant outcomes in newborns can be managed clinically and predicted perinatally using the DV Doppler examination.